Development of ligament tissue biodegradable devices: A review - Vieira, AC (2009)
This bibliographic review is focused on ligament tissue rehabilitation, its anatomy-physiology, and, mainly, on the dimensioning considerations of a composite material solution. The suture strength is problematic during the tissue recovering, implying reduction of mobility for several months. However, early postoperative active mobilization may enable a faster and more effective recovering of tissue biomechanical functions. As the risk of tendon rupture becomes a significant concern, a repair technique must be used to withstand the tensile forces generated by active mobilization. However, to avoid stress shielding effect on ligament tissue, an augmentation device must be designed on stiffness basis, that preferably will decrease. Absorbable biocomposite reinforcements have been used to allow early postoperative active mobilization and avoid the shortcomings of current repair solutions. Tensile strength decrease of the repair, during the initial inflammatory phase, is expected, derived from oedema and tendon degradation. In the fibroblastic phase, stiffness and strength will increase, which will stabilize during the remodeling phase. The reinforcement should be able to carry the dynamic load due to locomotion with a mechanical behavior similar to the undamaged natural tissue, during all rehabilitation process. Moreover, the degradation rate Must also be compatible with the ligament tissue recovering. The selection and combination of different biodegradable materials, in order to make the biocomposite reinforcement functionally compatible to the damaged sutured tissue, in terms of mechanical properties and degradation rate, is a major step on the design process. Modelling techniques allow pre-clinical evaluation of the reinforcement functional compatibility, and the optimization by comparison of different composite solutions in terms of biomechanical behavior.